1981
DOI: 10.1007/bf01870415
|View full text |Cite
|
Sign up to set email alerts
|

On the redox reactions and accessibility of amphiphilic flavins in artificial membrane vesicles

Abstract: Summary. (Photo-)redox reactions of different amphiphilic flavins bound to artificial membrane vesicles made from three different, saturated phospholipids have been investigated and compared with those of isotropically dissolved flavin. By means of C18-hydrocarbon chains, substituted at different positions, the flavin nucleus can be specifically oriented within the membrane, thereby imposing sterically anisotropic environments, which are liable to control flavin (photo-) chemistry. A spectrophotometric setup w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Note, photoreduction by both exogeneous EDTA and the intrinsic donor (cf. [41]) follow exactly the same iodide dependence, indicating that the availability of the electron donor is not rate limiting differences in the mechanisms of photoreduction by the intrinsic donor between natural lipids (Fig. 7B) and synthetic lipids (Fig.…”
Section: Quenching Of Vesicle-associated Flavin By Iodidementioning
confidence: 54%
See 4 more Smart Citations
“…Note, photoreduction by both exogeneous EDTA and the intrinsic donor (cf. [41]) follow exactly the same iodide dependence, indicating that the availability of the electron donor is not rate limiting differences in the mechanisms of photoreduction by the intrinsic donor between natural lipids (Fig. 7B) and synthetic lipids (Fig.…”
Section: Quenching Of Vesicle-associated Flavin By Iodidementioning
confidence: 54%
“…In a previous paper we demonstrated that vesicle-bound amphiphilic flavin could be reduced by an intrinsic donor in the gel state of the membrane as well as by exogeneous EDTA in the liquid crystalline state [41]. Surprisingly, both photoreduction mechanisms for the DPL/AF1 3 system, although obviously different, display precisely the same pattern of quenching by iodide (Fig.…”
Section: Quenching Of Vesicle-associated Flavin By Iodidementioning
confidence: 68%
See 3 more Smart Citations